Recombination at mammalian telomeres: an alternative mechanism for telomere protection and elongation. - Tarsounas, M; West, S (2005)
In human cells, homologous recombination (HR) provides an accurate mechanism for the repair of DNA double-strand breaks caused by replication fork breakdown or DNA damaging agents. HR also plays a role in the maintenance of eukaryotic telomeres; cells defective in the recombinational repair proteins RAD51D or RAD54 exhibit telomere shortening and end-to-end chromosome fusions. Here we discuss the way in which HR contributes to telomere protection and elongation in mammalian cells. Understanding the mechanisms by which HR promotes telomere maintenance has important implications for genomic stability and tumorigenesis.